2000
DOI: 10.1038/sj.neo.7900115
|View full text |Cite
|
Sign up to set email alerts
|

RhoC GTPase Overexpression Modulates Induction of Angiogenic Factors in Breast Cells

Abstract: Inflammatory breast cancer (IBC) is a distinct and aggressive form of locally advanced breast cancer. IBC is highly angiogenic, invasive, and metastatic at its inception. Previously, we identified specific genetic alterations of IBC that contribute to this highly invasive phenotype. RhoC GTPase was overexpressed in 90% of archival IBC tumor samples, but not in stage-matched, non-IBC tumors. To study the role of RhoC GTPase in contributing to an IBC-like phenotype, we generated stable transfectants of human mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 34 publications
8
116
1
1
Order By: Relevance
“…For instance, overexpression of RhoC was found in metastatic lesions of inflammatory breast cancer and pancreatic ductal adenocarcinoma (Suwa et al, 1998;Fritz et al, 2002;Kleer et al, 2002), and upregulation was associated with tumour progression in ovarian carcinoma (Horiuchi et al, 2003). While the molecular mechanism by which RhoC facilitates tumour metastasis remains to be determined, it is possible that increased expression of RhoC could result in: (1) disruption of cell polarity, which plays an important role in the epithelial -mesenchymal transition observed in more aggressive tumours (Zondag et al, 2000); (2) contribution to the loss of adherens junctions (Braga et al, 2000); (3) increase motility and ability to remould the extra-cellular matrix, which is required for tumour cells to become locally invasive (Khanna et al, 2001); and (4) increase in angiogenic factors that would result in promotion of vascularisation in tumour and increase the likelihood of tumour cell entering the bloodstream (van Golen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, overexpression of RhoC was found in metastatic lesions of inflammatory breast cancer and pancreatic ductal adenocarcinoma (Suwa et al, 1998;Fritz et al, 2002;Kleer et al, 2002), and upregulation was associated with tumour progression in ovarian carcinoma (Horiuchi et al, 2003). While the molecular mechanism by which RhoC facilitates tumour metastasis remains to be determined, it is possible that increased expression of RhoC could result in: (1) disruption of cell polarity, which plays an important role in the epithelial -mesenchymal transition observed in more aggressive tumours (Zondag et al, 2000); (2) contribution to the loss of adherens junctions (Braga et al, 2000); (3) increase motility and ability to remould the extra-cellular matrix, which is required for tumour cells to become locally invasive (Khanna et al, 2001); and (4) increase in angiogenic factors that would result in promotion of vascularisation in tumour and increase the likelihood of tumour cell entering the bloodstream (van Golen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The SUM149s are a reliable model of IBC, often reflecting what is observed in patient samples (11,12,17,(26)(27)(28)(29)(30)(31). Figure 2A is western blot analysis of individual Akt isoform protein expression and phosphorylation.…”
Section: Expression Of Active Akt In Ibc Cellsmentioning
confidence: 99%
“…RhoC GTPase overexpression leads to transformation of immortalized human mammary epithelial cells with an invasive phenotype similar to that of IBC (17). RhoC also promotes metastasis in other invasive cancers, including pancreatic ductal adenocarcinoma (18), lung cancer (19), and melanoma (20).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stable overexpression of RhoC confers a malignant phenotype to otherwise nontransformed human mammary epithelial cells (van Golen et al, 2000). Mira et al (2000) demonstrated that Rac3 is hyperactive in rapidly proliferating breast cancer cells, where it appears to be necessary for G1 to S phase transition.…”
Section: Introductionmentioning
confidence: 99%